Training Inhibitory Control Induced Robust Neural Changes When Behavior Is Affected: A Follow-up Study Using Cognitive Event-Related Potentials. (September 2020) - Schroder, Elisa; Dubuson, Macha; Dousset, Clémence; Mortier, Elena; Kornreich, Charles; Campanella, Salvatore
Cognitive training results in significant, albeit modest, improvements in specific cognitive functions across a range of mental illnesses. Inhibitory control, defined as the ability to stop the execution of an automatic reaction or a planned motor behavior, is known to be particularly important for the regulation of health behaviors, including addictive behaviors. For example, several studies have indicated that inhibitory training can lead to reduced alcohol consumption or a loss of weight/reduced energy intake. However, the exact neurocognitive mechanisms that underlie such behavioral changes induced by training are still matter of debate. In the present study, we investigated the long-term impact (ie, at 1 week posttraining) of an inhibitory training program (composed of 4 consecutive daily training sessions of 20 minutes each) on the performance of a Go/No-go task. Healthy participants were randomly assigned to 1 of 3 designated groups: (1) an Inhibition Training (IT) group that received training based on a hybrid flanker Go/No-go task; (2) a group that received a noninhibition-based (ie, episodic memory; EM) training; and (3) a No-Training (NT) group to control for test-retest effects. Each group underwent 3 sessions of a Go/No-go task concomitant with the recording of event-related potentials. Our results revealed a specific impact of the Inhibitory Training on the Go/No-go task, indexed by a faster process compared with the other 2 groups. This effect was neurophysiologically indexed by a faster N2 component on the difference NoGo-Go waveform. Importantly, effects at both the behavioral and at the neural level were still readily discernible 1 week posttraining. Thus, our data clearly corroborate the notion that cognitive training is effective, while also indicating that it may persist over time.